Research on ecological management zoning in Jilin Province based on a human well-being framework - Baihao Zhang; Jiafu Liu; Zhenyu Zhang; Yu Zhu (Scientific Reports)
Abstract Taking Jilin Province in 2020 as the study area, this research categorizes ecosystem service supply and demand by integrating ecosystem service functions with a human well-being framework. The study evaluates the supply and demand of ecosystem services and examines their spatial distribution characteristics. To further delineate ecological management zones, the SC K-means clustering algorithm and the coupling coordination degree model are employed. The results reveal significant regional disparities in the availability and necessity of six ecosystem services. Food production services exhibit a spatial pattern characterized by an increase in the central region while declining in the eastern and western areas. In contrast, the supply of the other five ecosystem services generally follows a “low in the west, high in the east” trend. Additionally, except for soil conservation, the demand for ecosystem services demonstrates a distribution pattern of being high in the central region and lower in the surrounding areas. The overall supply of ecosystem services gradually increases from west to east, reaching its peak in the eastern region, whereas the comprehensive demand is highest in the central region and lower in both the eastern and western areas, with central cities and their surrounding counties exhibiting the most pronounced demand. Based on the dynamics of supply and demand, Jilin Province is divided into five ecological management zones. The ecological potential zone, where supply–demand coordination transitions from low to high, is suited for developing green agricultural economies and optimizing industrial structures. The ecological restoration zone, experiencing a shift from high to low supply–demand balance, faces imbalances that necessitate efforts to alleviate human-land conflicts and enhance the equilibrium between social development and ecological conservation. The ecological consolidation zone, which maintains a high-to-low supply–demand trend with relative stability, requires continued efforts in preserving its natural environment. The ecological adjustment zone, characterized by an imbalanced high-to-low supply–demand transition, should focus on industrial restructuring and eco-tourism development. Lastly, the ecological coordination zone, which maintains a well-balanced supply–demand relationship, should leverage its economic foundation to advance environmental protection technologies and strengthen conservation efforts. This study provides a systematic evaluation of the spatial patterns of ecosystem service supply and demand in Jilin Province and offers targeted ecological management strategies to promote sustainable environmental development.